2014
DOI: 10.1101/003103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of alternating red and blue light irradiation generated by light emitting diodes on the growth of leaf lettuce

Abstract: Because global climate change has made agricultural supply unstable, plant factories are expected to be a safe and stable means of food production. As the light source of a plant factory or controlled greenhouse, the light emitting diode (LED) is expected to solve cost problems and promote plant growth efficiently. In this study, we examined the light condition created by using monochromatic red and blue LEDs, to provide both simultaneous and alternating irradiation to leaf lettuce. The result was that simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…1). The DLIs of all light sources were set to 6.9 mol · m -2 · d -1 in all of the following six light conditions according to Shimokawa et al (2014) (Fig. 1): (1) constant white light at 80 mmol · m -2 · s -1 (W24); (2) constant red and blue light at 120 mmol · m -2 · s -1 for 12 h and 40 mmol · m -2 · s -1 for 12 h (RB12/12); (3) constant red and blue light at 80 mmol · m -2 · s -1 (RB24); (4) red and blue light for 16 h at 120 mmol · m -2 · s -1 (RB16); (5) alternating red light at 80 mmol · m -2 · s -1 for 18 h and blue light at 80 mmol · m -2 · s -1 for 6 h (R18/B6); and (6) alternating red light at 120 mmol · m -2 · s -1 for 12 h and blue light at 40 mmol · m -2 · s -1 for 12 h (R12/B12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The DLIs of all light sources were set to 6.9 mol · m -2 · d -1 in all of the following six light conditions according to Shimokawa et al (2014) (Fig. 1): (1) constant white light at 80 mmol · m -2 · s -1 (W24); (2) constant red and blue light at 120 mmol · m -2 · s -1 for 12 h and 40 mmol · m -2 · s -1 for 12 h (RB12/12); (3) constant red and blue light at 80 mmol · m -2 · s -1 (RB24); (4) red and blue light for 16 h at 120 mmol · m -2 · s -1 (RB16); (5) alternating red light at 80 mmol · m -2 · s -1 for 18 h and blue light at 80 mmol · m -2 · s -1 for 6 h (R18/B6); and (6) alternating red light at 120 mmol · m -2 · s -1 for 12 h and blue light at 40 mmol · m -2 · s -1 for 12 h (R12/B12).…”
Section: Methodsmentioning
confidence: 99%
“…Jao and Fang (2004) reported that alternating red and blue light reduced growth of potato plantlets relative to simultaneous red and blue light. On the other hand, Shimokawa et al (2014) and Chen et al (2017) reported that alternating red and blue light could affect growth of lettuce, but the authors could not conclude whether it had benefit for plant growth compared with simultaneous red and blue light because the growth period was short or the daily light integral (DLI) and day length were not comparable among treatments. Recently, Kuno et al (2017) showed that alternating red and blue light could enhance growth in leafy lettuce compared with simultaneous red and blue light under equal DLI and day length, but Jishi et al (2016) showed the opposite result in cos lettuce.…”
mentioning
confidence: 99%
“…We conducted experiment 2 to determine whether the cause of growth promotion is due not to prolongation of day length but the shift in irradiation times. Table 4 shows that alternating irradiation with red and blue lights for 12-h periods promoted lettuce growth more effectively than did simultaneous irradiation for 24 h. Further, the cultivation experiment examining the effects of simultaneous, and alternating irradiations with red and blue light on leaf lettuce growth demonstrated that a pattern of alternating irradiation between red and blue light enhanced lettuce growth most effectively, when the fresh weight of lettuce plants under alternating irradiation regimes was about 1.6 times larger than the fresh weight of plants grown under simultaneous irradiation (Shimokawa et al, 2014), and Ohtake et al (2014; showed alternating irradiation with red and blue light increased fresh weight of leaf lettuce compared to simultaneous light. Alternating irradiation between red and blue lights is thus more effective at promoting Greenwave than is simultaneous irradiation.…”
Section: Effects Of Simultaneous or Alternating Irradiation Of Red Anmentioning
confidence: 97%
“…In addition, the rhythm of these processes can change periodically during a single day. Previous lighting strategies have ignored the effects of photoperiod on circadian rhythm, missing the opportunity to use the circadian rhythm to benefit the growth of crops in PFALs [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%